The visionary executive strategic planning for the new business leaders - Brooke, Michael Z. (AMACOM, 1998)
What distinguishes the successful business leader is vision. The Visionary Executive, written from a global perspective, will help you achieve substantial results by demonstrating: what it takes to be a visionary leader, how to focus the vision, based on information and objectives, how to predict the competition's vision and stay steps ahead.